2021
DOI: 10.1039/d1py00101a
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt catalysed controlled copolymerization: an efficient approach to bifunctional polyisoprene with enhanced properties

Abstract: Preparation of functional polyisoprene via direct catalytic insertion polymerization has been preferred because the polymers’ regularity, molar mass and functionality can be facilely controlled by catalyst. However, this method has...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 60 publications
0
41
0
Order By: Relevance
“…However, this method poses critical challenges including loss of activity, poor control of the functional degree, and chain transfer and termination reactions associated with the detrimental effect of the functional group. 279 Mecking et al synthesized stereoregular trans-1,4-poly-(dienes) with three different types of functional groups by insertion polymerization. The functional groups were located simultaneously in the polymer backbone and at both chain ends, yielding heterotelechelic and in-chain-functionalized polymers.…”
Section: Stereoblock Diene Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this method poses critical challenges including loss of activity, poor control of the functional degree, and chain transfer and termination reactions associated with the detrimental effect of the functional group. 279 Mecking et al synthesized stereoregular trans-1,4-poly-(dienes) with three different types of functional groups by insertion polymerization. The functional groups were located simultaneously in the polymer backbone and at both chain ends, yielding heterotelechelic and in-chain-functionalized polymers.…”
Section: Stereoblock Diene Polymersmentioning
confidence: 99%
“…The functional copolymers show significantly improved hydrophilicity and good thermal properties useful for application in the rubber industry. 285…”
Section: Stereoblock Diene Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Gong et al also reported on the synthesis of bifunctional monomers dienes derivatives (hydroxyl, furan and pyridine group) obtained from bio-sourced M and their controlled copolymerization with I via catalytic insertion mechanism. [67] A series of new Co-based complexes (51-55) (Figure 12) were tested, providing yields in most cases above 90 % in about 1 h. Copolymerization followed a first-order kinetics dependence on monomer without obvious chain transfer and termination. The role of the labile arm in inhibiting chain transfer reaction has also been hypothesized.…”
Section: Cobaltmentioning
confidence: 99%
“…Similar to polar polyolefin materials, functionalized Polymers 2021, 13, 3329 2 of 11 polydienes elastomers are also of great significance because the incorporated functional groups can greatly improve the compatibility between the polydienes matrix and reinforce polar fillers, such as carbon black, silica, etc., which therefore produces well-performing elastomers with good modulus, tensile strength, and other dynamic mechanical properties [13]. However, research n copolymerization with polar copolymers in this field o is very limited [14,15]. In the present research, a series copolymerizations of 1,3-butadiene with polar comonomer 2-(4-methoxyphenyl)-1,3-butadiene (2-MOPB) is conducted, and the corresponding catalytic performances and microstructures of the resulting copolymers are discussed.…”
Section: Introductionmentioning
confidence: 99%